Gynecomastia disclosing diagnosis of Leydig cell tumour in a man withthalassemia, secondary hypogonadism and testis microlithiasis - Wasniewska, M.; Raiola, G.; Arrigo, T.; Galati, et al., M. C. (Acta Biomedica Atenei Parmensis, 2009)
Aim of this paper is to report about a 35-year old man suffering from β-Thalassemia major and longstanding untreated hypogonadotropic hypogonadism, who was referred because of a recent onset and painful bilateral gynecomastia, with no palpable testicular masses. Due to the finding of a solid mass at left testis ultrasonography, monolateral testicular exeresis was performed and histology revealed a Leydig Cell Tumour and testicular microlithiasis. Post-surgical restoration of testosterone/estradiol ratio under testosterone therapy was followed by a very rapid reduction of gynecomastia. Our report confirms the usefulness of scrotal ultrasonography for finding an occult testicular tumour in a patient with painful and recent onset bilateral gynecomastia and underlines: a) the important role of testosterone/estradiol ratio in the pathophysiology of gynecomastia; b) the questionable significance of testicular microlithiasis as marker of testis tumours; c) the possible association between β-Thalassemia and tumoral pathologies.